Especiação de compostos de arsênio em águas e fluidos biológicos empregando pré-tratamento fotoquímico e métodos voltamétricos - Stefanello, Raquel (2007)
The presence of arsenic as a contaminant in water and biological fluids has been studied in recent years due to the high toxicity of this element. In this work a method for the selective determination of arsenic species was developed, which is based on the determination of As(III) directly in the samples and on the determination of total arsenic after a photochemical pretreatment step. For the determination of As(III), different voltammetric methods have been used: the Adsorptive Cathodic Stripping Voltammetry (AdCSV), the Cathodic Stripping Voltammetry (CSV) and Anodic Stripping Voltammetry (ASV). Amongst the studied methods, the ASV, using a gold electrode, showed to be highly sensitive and reproducible, with a detection limit of 0,2 μg L−1 and quantification limit of 0,5 μg L−1 calculated for arsenic. For the speciation between As(III) and As(V), a new procedure based on the photochemical pretreatment for the reduction of As(V) to As(III) in the presence of reducing sugars such as glucose was developed. Regarding the proposed mechanism for the photochemical pretreatment, it is suggested that reduction of As(V) to As(III) does not occur by direct action of glucose and even by the direct action of UV radiation. An indirect reduction process, which is induced by the glucose decomposition under UV irradiation, has been proposed. The experimental parameters irradiation time and glucose concentration were systematically investigated. The reduction of As(V) to As(III) was achieved with about 100% efficiency in the presence of glucose 60 mg L−1, which was added to the solution containing As(V) and then it was irradiated for 90 minutes at a temperature of 85 °C. For the solutions with a high content of organic matter, a previous step prior to the reduction step was necessary for the sample decomposition and the elimination of the matrix interference. Recovery experiments for As(III) and As(V) were carried out in spiked samples. The recovery results for total arsenic total were above 80%, confirming the applicability of the procedure involving the photochemical pretreatment for the arsenic speciation in samples of waters and biological fluids.